Air Quality Conditions (NO2) Around the Konawe Industrial area and the Resulting Respiratory Problems - Rauf, Rahman; Amraeni, Yunita; Azizi Jayadipraja, Erwin (Waluya The International Science of Health Journal, 2023)
Introduction: Air quality is strongly influenced by activities carried out by humans. This study aims to determine the NO2 air quality around the Konawe industrial area as well as community activities and respiratory disorders experienced. Method: The data used is a linear regression statistical test to determine the relationship between NO2 air quality with community activity and respiratory disorders. Result: This research was conducted in 6 villages around the Konawe industrial area. Most people carry out their daily activities around the industrial area, so some people experience respiratory problems. In the regression analysis, it is known that the activities of residents of the house affect the concentration of NO2 by 4% and the concentration of these pollutants affects the respiratory disorders of residents of the house by 25%. Conclusion: The conclusion in this journal is that smoking activity in the house is not related to the concentration of NO2 in the air and respiratory problems experienced by residents of the house are also not related to the concentration of NO2 in the house. This study provides awareness that air quality in the house is important to maintain the health of residents of the house and to provide input for residents of the house to reduce activities that can interfere with air quality in closed rooms.